2018
DOI: 10.1016/j.euroneuro.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Functional mechanism of ASP5736, a selective serotonin 5-HT5A receptor antagonist with potential utility for the treatment of cognitive dysfunction in schizophrenia

Abstract: The 5-HT receptor is arguably the least understood 5-HT receptor. Despite widespread expression in human and rodent brains it lacks specific ligands. Our previous results suggest that 5-HT receptor antagonists may be effective against cognitive impairment in schizophrenia. In this study, using behavioral, immunohistochemical, electrophysiological and microdialysis techniques, we examined the mechanism by which ASP5736, a novel and selective 5-HT receptor antagonist, exerts a positive effect in animal models of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Last but not least, data from this laboratory indicate that SB 699551 reversed ketamine-induced cognitive deficits in the attentional set-shifting test and novel object recognition task, as well as ketamine-induced social withdrawal in social interaction and in the social choice tests, suggesting that the 5-HT 5A receptor antagonist may ameliorate cognitive impairments and 'negative-like' symptoms (Nikiforuk et al, 2016). The procognitive effects of another 5-HT 5A receptor antagonist, ASP 5736, in the PCP-induced model of schizophrenia symptoms were recently reported by Yamazaki et al (2018). Altogether, these data suggest that 5-HT 5A receptor antagonists display some antipsychotic-like effects.…”
Section: Discussionmentioning
confidence: 79%
“…Last but not least, data from this laboratory indicate that SB 699551 reversed ketamine-induced cognitive deficits in the attentional set-shifting test and novel object recognition task, as well as ketamine-induced social withdrawal in social interaction and in the social choice tests, suggesting that the 5-HT 5A receptor antagonist may ameliorate cognitive impairments and 'negative-like' symptoms (Nikiforuk et al, 2016). The procognitive effects of another 5-HT 5A receptor antagonist, ASP 5736, in the PCP-induced model of schizophrenia symptoms were recently reported by Yamazaki et al (2018). Altogether, these data suggest that 5-HT 5A receptor antagonists display some antipsychotic-like effects.…”
Section: Discussionmentioning
confidence: 79%
“…In our previous study, we showed that 0.001–0.03 mg/kg of ASP5736 was effective for improving cognitive performance in the water maze task in aged rats, with a maximum effect observed at 0.01 mg/kg ( Yamazaki et al, 2015 ). In a separate study ( Yamazaki et al, 2018 ), we showed that ASP5736 (0.001–0.01 mg/kg, po) significantly improved cognitive deficits exhibited by a subchronical phencyclidine-induced rat model in the attentional set-shifting task, with a maximum effect also observed at 0.01 mg/kg. A study by Ventura et al (2004) demonstrated that amphetamines improve the ability of Fmr1 -KO mice to discriminate between novel and familiar objects without significantly affecting locomotor activity.…”
Section: Discussionmentioning
confidence: 89%
“…We previously demonstrated that ASP5736, a 5-HT 5A receptor antagonist, ameliorated scopolamine-induced working memory deficits in mice, reference memory impairment in aged rats ( Yamazaki et al, 2015 ), and methamphetamine-induced positive symptoms ( Yamazaki et al, 2014 ) and phencyclidine-induced cognitive impairment in animal models of schizophrenia ( Yamazaki et al, 2018 ). Here, we characterized several behaviors of male Fmr1 -KO rats as an alternative preclinical model of FXS and evaluated the effects of ASP5736 in the male Fmr1 -KO rat model.…”
Section: Introductionmentioning
confidence: 99%
“…While our study identified BDNF dysfunction as a key mechanism that contributes to the impact of subchronic PCP administration on PFC function, other mechanisms are also involved. This includes, for example, dysfunction of the dopaminergic (Balla et al, 2003; Jentsch, 1997; McLean et al, 2017), GABAergic (Amitai et al, 2012; Dawson et al, 2014; Gong et al, 2009) and serotonergic (Hori et al, 2000; Santini et al, 2013; Yamazaki et al, 2018) systems. Interestingly, there is also some evidence that these neurotransmitter systems regulate BDNF function (Fumagalli et al, 2006; Porcher et al, 2018), therefore future characterisation of the inter-related nature of these mechanisms in the PCP mouse model would be of interest.…”
Section: Discussionmentioning
confidence: 99%